Stage fright [video recording] - Centron Films (Deerfield, Illinois Centron Educational Films, 1979)
Bernie Greenland, ordinarily a happy man, becomes panic-stricken when he is asked to address a club luncheon. Bernie's plight is not unusual, but there are specific techniques that Bernie or any speaker can apply to successfully control and harness stage fright. Explores the physiology and psychology of this very real malady. From the Art of communication series.
Distributed by International Book Center.
Keywords: Stage fright; Stage anxiety